Comparison of Periodontal Bacteria of Edo and Modern Periods Using Novel Diagnostic Approach for Periodontitis With Micro-CT - Shiba, Takahiko; Komatsu, Keiji; Sudo, Takeaki; Sawafuji, Rikai; Saso, Aiko; Ueda, Shintaroh; Watanabe, Takayasu; Nemoto, Takashi; Kano, Chihiro; Nagai, Takahiko; Ohsugi, Yujin; Katagiri, Sayaka; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Ancient dental calculus, formed from dental plaque, is a rich source of ancient DNA, and can provide information regarding the food and oral microbiology at that time. Genomic analysis of dental calculus from Neanderthals has revealed the difference in bacterial composition of oral microbiome between Neanderthals and modern humans. There are few reports investigating whether the pathogenic bacteria of periodontitis, which is a polymicrobial disease induced in response to the accumulation of dental plaque, were different between ancient and modern humans. This study aimed to compare the bacterial composition of the oral microbiome in ancient and modern human samples and to investigate whether lifestyle differences depending on the era has altered the bacterial composition of oral microbiome and the causative bacteria of periodontitis. Additionally, we introduce a novel diagnostic approach for periodontitis in ancient skeletons using micro-computed tomography. Ancient 16S rDNA sequences were obtained from 12 samples at the Unko-in site (18th-19th century) of the Edo era (1603–1867), a characteristic period in Japan when immigrants were not accepted. Furthermore, modern 16S rDNA data from 53 samples were obtained from a database to compare the modern and ancient microbiome. The microbial co-occurrence network was analysed based on 16S rDNA read abundance. Eubacterium species, Mollicutes species, and Treponema socranskii were the core species in the Edo co-occurrence network. The co-occurrence relationship between Actinomyces oricola and Eggerthella lenta appeared to have played a key role in causing periodontitis in the Edo era. However, Porphyromonas gingivalis, Fusobacterium nucleatum subsp. vincentii, and Prevotella pleuritidis were the core and highly abundant species in the co-occurrence network of modern samples. These results brought us to the conclusion that there is the possibility of differences in the pathogens causing periodontitis during different eras in history.